HER2/neu expression correlates with vasculogenic mimicry in invasive breast carcinoma. Issue 1 (19th December 2012) - Liu, Tieju; Sun, Baocun; Zhao, Xiulan; Gu, Qiang; Dong, Xueyi; Yao, Zhi; Zhao, Nan; Chi, Jiadong; Liu, Ning; Sun, Ran; Ma, Yuemei
Abstract Vasculogenic mimicry (VM) refers to the condition in which tumour cells mimic endothelial cells to form extracellular matrix‐rich tubular channels. VM is more extensive in more aggressive tumours. The human epidermal growth factor receptor 2 (HER2) gene is amplified in 20–30% of human breast cancers and has been implicated in mediating aggressive tumour growth and metastasis. However, thus far, there have been no data on the role of HER2 in VM formation. Immunohistochemical and histochemical double‐staining methods were performed to display VM in breast cancer specimens. Transfection in MCF7 cells was performed and clones were selected by G418. The three‐dimensional Matrigel culture was used to evaluate VM formation in the breast cancer cell line. According to statistical analysis, VM was related to the presence of a positive nodal status and advanced clinical stage. The positive rate of VM increased with increased HER2 expression. In addition, cases with HER2 3+ expression showed significantly greater VM channel count than those in other cases. The exogenous HER2 overexpression in MCF‐7 cells induced vessel‐like VM structures on the Matrigel and increased the VM mediator vascular endothelial (VE) cadherin. Our data provide evidence for a clinically relevant association between HER2 and VM in human invasive breast cancer. HER2 overexpression possibly induces VM through the up‐regulation of VE cadherin. Understanding the key molecular events may provide therapeutic intervention strategies for HER2+ breast cancer.